The Examination of Psychological Factors and Social Norms Affecting Body Satisfaction and Self‐Esteem for College Students. (June 2017) - Chang, Hyo Jung (Julie); Suttikun, Chompoonut
Abstract : The purpose of this study was to investigate the effects of exercise self‐efficacy, weight concerns, self‐fulfillment, and social norms on college students' body satisfaction and self‐esteem. Also, the study examined the relationship between body satisfaction and self‐esteem. An online survey was used, and 187 college students participated in the study. The findings revealed that exercise self‐efficacy positively influenced college students' body satisfaction, while weight concerns negatively influenced college students' body satisfaction. Exercise self‐efficacy and self‐fulfillment positively influenced self‐esteem while social norms negatively influenced self‐esteem. Exercise self‐efficacy had the most significant positive effect on body satisfaction while social norms had the most significant negative effect on self‐esteem. The results could help exercise facilities learn what to include in their programs to increase college students' psychological well‐being, including body satisfaction and self‐esteem.